Single Nucleotide Polymorphism Facilitated Down-Regulation of the Cohesin Stromal Antigen-1: Implications for Colorectal Cancer Racial Disparities - Datta, Somenath (Neoplasia, 2018)
The biological underpinnings for racial disparities in colorectal cancer (CRC) incidence remain to be elucidated. We have previously reported that the cohesin SA-1 down-regulation is an early event in colon carcinogenesis which is dramatically accentuated in African-Americans. In order to investigate the mechanism, we evaluated single nucleotide polymorphisms (SNPs) for association with SA-1-related outcomes followed by gene editing of candidate SNP. We observed that rs34149860 SNP was significantly associated with a lower colonic mucosal SA-1 expression and evaluation of public databases showed striking racial discordance. Given that the predicted SNP would alter miR-29b binding site, we used CRISPR knock-in in CRC cells and demonstrated that the SNP but not wild-type had profound alterations in SA-1 expression with miR-29b inhibitor. This is the first demonstration of high-order chromatin regulators as a modulator of racial differences, risk alteration with SNPs and finally specific modulation by microRNAs.